Martin Trow's elite‐mass‐universal triptych: Conceptualising Higher Education development. (12th July 2019) - Scott, Peter
Abstract: Martin Trow was among the most influential scholar in Higher Education studies in the second half of the 20th century. He is best known for his conceptualisation of the development of Higher Education into three stages—elite, mass and universal systems. This article considers, first, his intellectual method and the underpinning theory (or lack of it); secondly, the extent to which his ideas, generated in the exceptional environment of post‐war America were, and are, relevant to different national contexts and in the very different environment of the 21st century; thirdly, the strengths—and weaknesses—of Trow's conceptualisation of three stages of Higher Education development; and, finally the new lines of research suggested by an overall assessment of his work. Abstrait: Martin Trow était l'un des érudits les plus influents de l'enseignement supérieur de la seconde moitié du XXe siècle. Il est surtout connu pour sa conceptualisation du développement de l'enseignement supérieur en trois étapes: systèmes élite, systèmes de masse et systèmes universels. Cet article considère, en premier lieu, sa méthode intellectuelle et la théorie sous‐jacente (ou son absence); deuxièmement, la mesure dans laquelle ses idées, générées dans l'environnement exceptionnel de l'Amérique d'après‐guerre, étaient et sont pertinentes pour différents contextes nationaux et dans l'environnement très différent du XXIe siècle; troisièmement, les forces et les faiblesses de la conceptualisation par Trow de trois étapes du développement de l'enseignement supérieur; et, enfin, les nouvelles pistes de recherche suggérées par une évaluation globale de son travail.